Children Under Five Years of Age: Factor Analysis of Tuberculosis Preventive Therapy's Success in Controlling Childhood Tuberculosis - Wahyuningsih, dr. Rita; Syafriadi, Mei; Mufida, Diana Chusna (Journal of Agromedicine and Medical Sciences, 2025)
Jember Regency is the 2nd Regency after Surabaya City in finding the highest number of TB cases in East Java Province, with 5,244 adult cases and 478 pediatric TB cases found. Finding TB cases in children is an important component in controlling TB because the number of children aged less than 14 years constitutes 12% of the population. The government's efforts to control childhood TB by providing TPT (TPT) as an effort to strengthen the management of latent tuberculosis infection (ILTB) are still low. Toddlers in close contact with Drug Sensitive Tuberculosis (TB SO) are a group at risk of being infected with TB so they need to get TPT. This study aims to determine and analyze the driving factors, enabling factors, reinforcing factors and the role of the Medication Supervisor (PMO) on medication adherence in the TPT program for toddlers in close contact with TB in Jember Regency. The method in this research uses the Explanatory Research type, which is a type of research that aims to analyze the relationship or influence between variables through hypothesis testing. The results of this research indicate that the success factors of the TPT administration program, namely driving factors, enabling factors, reinforcing factors and the role of the Medication Supervisor (PMO) are proven to influence medication adherence in the TPT administration program for toddlers in close contact. It’s known that the factors contributed mainly to the successness of Tuberculosis Prevention Therapy are family’s support and the rile of the the Medication Supervisor (PMO).